EFFECT OF LUMBAR STABILIZATION EXERCISES VERSUS PRESSURE FEEDBACK TRAINING IN LOW BACK ACHE PATIENTS - Shadab Uddin; Fuzail Ahmed (European Scientific Journal, ESJ, 2013)
Chronic low back pain is the most common complaints in the urban society causing to absent from the work and activity limitation. Its health, social and economic burden is hefty. Despite developments in modern medicine in general and growing knowledge of spinal diseases, problem of nonspecific low back pain remains unsolved. Although the nonspecific types of bach pain affects approximately 85% of patients while 40% of low back pain patients worry that pain affects their work ability and will make them cripple, or that it underlies some serious disese (Waddell 1998). Even though there is ample evidence stating the efficacy of core stability training but not able to find any study which has compared Pressure Biofeedback training with Core Stability Training in the treatment of chronic low back pain. The aim of the present study was to compare the effectiveness of stabilizer pressure biofeedback training and core stability exercises on pain perception as measure by visual analogue scale in chronic low back pain patients.